VALUE CHAIN AND CRITICAL SUCCESS FACTORS FOR THE ADVERTISING AGENCY IN TURKEY'S ADVERTISING INDUSTRY - KOÇ, Murat; ÖZBOZKURT, Onur Başar (Acta Scientiae et Intellectus, 2024)
Today, businesses are increasing the importance of competition in terms of advertising. Businesses are admitted advertising market share increases. Advertising is one of the most significant elements of the competitive factors, which most effective way to reach consumers. Businesses come in contact with advertising agencies to advertise, directly or indirectly. Giving ad should be considered as a process. After the selection of the agency carefully planned and programmed process monitoring, it is important for advertisers. Thus, the choice of the appropriate agencies be approached by reducing the failure condition in the selection of advertising agencies. Some of the critical success factors are also important for advertisers appointed in and found successful advertising agencies. On the other hand, many sectors are mobilizing along with many actors playing a role, which is at the forefront of creativity in the advertising industry. This study was aimed to determine the critical success factors in terms of advertising agencies, to reveal the advertising industry value chain analysis in Turkey.